Response of Polycrystalline Solar Cell Outputs to Visible Spectrum and other Light Sources-a Case Study - Ayman Y. Al-Rawashdeh; Omar Albarbarawi; Ghazi Qaryouti (International Journal of Electrical and Computer Engineering (IJECE), 2018)
In this case study, two polycrystalline solar modules were installed outdoors (irradiated by sunlight) and indoors (irradiated by artificial lights). The solar cells in both cases were installed using different color filters that allowed the passage of certain light frequencies. The amount of energy produced by each module were measured and compared to a reference module with no filter. The results indicated the variable response of polycrystalline solar cells to natural and artificial light sources, being more responsive in both cases to red band color as could be deduced from their % current outputs (72.5% sunlight radiation; 84.38% artificial light sources). Other colors, including yellow, green, orange and violet afforded acceptable outputs. The results indicated that electrical outputs of indoor solar cells decreased when colored filters were used, but red filter in general afforded the maximum outputs, for both the artificially radiated indoor and naturally radiated outdoor solar cells. The case study suggests the possible complementary advantage of using indoor mounted solar cells for the production of electricity during artificial illumination period of the day.